Peroxidative degradation of proteins and lipids in undifferentiated connective tissue dysplasia in children, Ukraine - Tetyana V. Pochynok; Maryna M. Vasiukova; Iryna S. Kudlatska-Tyshko (Narra J, 2021)
The aim of the study was to assess the state of lipid and protein peroxidation in children with undifferentiated connective tissue dysplasia (UCTD). In this study, 63 children (33 children with UCTD and 30 children without UCTD were recruited and the indicators of lipid and protein peroxidation were measured. The enzymatic, colorimetric method was used to measure the level of total cholesterol (TC). The phospholipids were analyzed by liquid chromatography/mass spectrometry using electrospray ionization. Lipid peroxidation was studied by assessing the change of index and the end product of lipid peroxidation, malondialdehyde (MDA), using spectrophotometric method. Protein peroxidation - by the content of carbonylated protein based on 2,4 dinitrophenyl-hydrazones derivatization. The activity of the antioxidant defense system enzymes was assessed by measuring catalase (CAT) and superoxide dismutase (SOD). Our study revealed a significant increase of PPO products in the venous blood plasma and LPO products in erythrocytes in children with UCTD. Furthermore, an imbalance of the antioxidant defense system was observed in both blood plasma and erythrocytes membrane.